Translation and Cultural Understanding: Bridging Languages, Identities, and Worldviews - Vijaykumar S. Meeshi, (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2026)
Translation is not merely a linguistic activity but a complex cultural, social, and ideological process that enables communication between diverse societies. It functions as a bridge through which histories, values, beliefs, ideologies, and identities travel across linguistic boundaries. In a multilingual and multicultural world marked by globalization, migration, and digital communication, translation plays a crucial role in fostering cultural understanding and dialogue. This paper examines translation as a cultural act rather than a mechanical transfer of words. Drawing on the theoretical insights of Eugene Nida, Susan Bassnett, Lawrence Venuti, Gayatri Chakravorty Spivak, and Edward Sapir, the paper explores how translation mediates culture, negotiates power relations, and represents marginalized voices. It further discusses the challenges faced by translators in conveying culturally specific concepts and examines the role of translation in promoting intercultural harmony, social inclusivity, and global knowledge exchange. The study argues that culturally sensitive and ethically responsible translation enhances mutual understanding by respecting linguistic diversity and cultural contexts.
Keywords: Translation; Culture; Cultural Understanding; Intercultural Communication; Identity; Power